THE DIFFICULTIES AND ADVANTAGES OF TEACHING A FOREIGN LANGUAGE - Raisov Shamsiddin, Raisov Shamsiddin (Журнал иностранных языков и лингвистики, 2021)
It is natural, of course, that the majority of students face difficulties in learning a foreign language. Teachers need to monitor where and how the students are experiencing difficulties and find ways to overcome it and seek for a way to create relaxation for the students.The article also provides information about the peculiarities of learning English.